The explanatory determinants of a successful mindfulness intervention in an ecuadorian university: a logit analysis - Méndez Prado, Silvia Mariela; Rosado Anastacio, Joel Alejandro (International journal of adolescence and youth, 2019)
This paper examines the success of a Mindfulness Intervention on 206 freshmen at the School of Social Sciences and Humanities of ESPOL, in Guayaquil-Ecuador by using logit analysis. The results show that age, gender, type of college, college´s location, number of mindfulness sessions, admission score, approved subjects, academic scores, people you live with, birth order, higher education career, play musical instrument, practice sport, and the use of glasses of the respondents have signiﬁcant effects on mindfulness practice. The contribution of the study remains as the observed effects might respond to a particular behavior of students of social sciences. A future approach may then include students from different areas and analyze if there are any differences among such groups.